High Glucose Increases Lactate and Induces the Transforming Growth Factor Beta-Smad 1/5 Atherogenic Pathway in Primary Human Macrophages - Awad, Kareem; Kakkola, Laura; Julkunen, Ilkka (MPDI, 2025)
Hundreds of millions of people worldwide are expected to suffer from diabetes mellitus. Diabetes is characterized as a dynamic and heterogeneous disease that requires deeper understanding of the pathophysiology, genetics, and metabolic shaping of this disease and its macro/microvascular complications. Macrophages play an essential role in regulating local immune responses, tissue homeostasis, and disease pathogenesis. Here, we have analyzed transforming growth factor beta 1 (TGFβ1)/Smad signaling in primary human macrophages grown in normal (NG) and high-glucose (HG; +25 mM glucose) conditions. Cell culture lactate concentration and cellular phosphofructokinase (PFK) activity were increased in HG concentrations. High glucose levels in the growth media led to increased macrophage mRNA expression of TGFβ1, and TGFβ-regulated HAMP and PLAUR mRNA levels, while the expression of TGFβ receptor II remained unchanged. Stimulation of cells with TGFβ1 protein lead to Smad2 phosphorylation in both NG and HG conditions, while the phosphorylation of Smad1/5 was detected only in response to TGFβ1 stimulation in HG conditions. The use of the specific Alk1/2 inhibitor dorsomorphin and the Alk5 inhibitor SB431542, respectively, revealed that HG conditions led TGFβ1 to activation of Smad1/5 signaling and its downstream target genes. Thus, high-glucose activates TGFβ1 signaling to the Smad1/5 pathway in primary human macrophages, which may contribute to cellular homeostasis in a harmful manner, priming the tissues for diabetic complications.